KAJIAN AKTIVITAS EKONOMI MASYARAKAT TERHADAP KELESTARIAN LINGKUNGAN CATHMENT AREA PLTA KOTO PANJANG – KABUPATEN KAMPAR - Zulkarnaini Zulkarnaini; Aras Mulyadi; Imam Deisy Mustiono (Jurnal Ilmu Lingkungan, 2010)
his study aims to identify and analyze the condition of land cover in the area of hydropowercathment Koto Panjang area based on Landsat image analysis in 2001 and 2008, knowing theeconomic activity undertaken by people who lived in the area of hydropower cathment KotoPanjang area and its influence on the preservation of the area cathment Hydroelectric KotoPanjang. The method used in this study is to survey, which collected data consists of primarydata and secondary data. Primary data were obtained from interviews and observations madeon society and the natural conditions in the village sample (Ranah Sungkai, Koto Tuo, Tabing)While secondary data obtained from the results of the study and documentation of variouspapres and official reports from various related agencies.Based on analysis of Landsat imagery in 2001 and in 2008, it is known that in the area ofhydropower cathment Koto Panjang area there are 12 land cover types, namely primary uplandforest, secondary upland forests, scrub / shrub, shrub / scrub wetlands, vegetation youngorderly, vegetation the old order, settlement, plantation, dry land farming, dry land farmingmixed with shrubs, open ground, and the water body itself. The forest area is an area thatexperienced the largest reduction of 15.55%. Meanwhile, scrub the area is an area thatexperienced the largest increase of 11.47%.Economic activities undertaken by the public within the area of hydropower cathment KotoPanjang area mostly gardening. Cultivated plantations dominated by rubber and oil palmplantations. Palm oil plantations started a trend by the public since the year 2004/2005 because t thinks the oil palm plantation is more profitable than rubber. While the rubber plant ingeneral they earn less attention to the rules of conservation of soil and water, where most of theterracing was not conducted on lands mostly ride a bicycle. In addition they earn rubbermonoculture is still, there is no innovation to be done heteroculture or agroforestry patterns thatare economically and ecologically more favorable course.